2020
DOI: 10.1080/2162402x.2020.1752563
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adjuvant cytokine-induced killer cell immunotherapy in patients with colorectal cancer after radical resection

Abstract: Adjuvant chemotherapy after surgery is the standard treatment modality for stage III and part of stage II or stage IV colorectal cancer (CRC) patients. However, the 5-year overall survival (OS) rate remains unsatisfactory. Thus, developing combination therapies is essential to improve the prognosis of patients with CRC. The present study aimed to determine the effect of a sequential combination of cytokine-induced killer cell (CIK) infusion and chemotherapy for patients with CRC. 122 patients with CRC treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 39 publications
(49 reference statements)
0
46
0
Order By: Relevance
“…Apart from single and combined therapies, the sequential use of chemotherapy, radiotherapy, targeted therapy followed by immunotherapy has been emerging as one of the latest choices in cancer treatment and proved to be more effective than immunotherapy alone by some previous study in lung cancer, colorectal cancer, hepatocellular carcinoma, and cholangiocarcinoma (13)(14)(15)(16)(17). However, the sequential use of chemotherapy and immunotherapy in osteosarcoma has never been reported, and only in vitro evidence became available very recently, showing that checkpoint blockade in combination with doxorubicin augments tumor cell apoptosis (18), and neoadjuvant chemotherapy reprogrammed the tumor immunologic microenvironment and facilitated the subsequent immunotherapy in osteosarcoma (19).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from single and combined therapies, the sequential use of chemotherapy, radiotherapy, targeted therapy followed by immunotherapy has been emerging as one of the latest choices in cancer treatment and proved to be more effective than immunotherapy alone by some previous study in lung cancer, colorectal cancer, hepatocellular carcinoma, and cholangiocarcinoma (13)(14)(15)(16)(17). However, the sequential use of chemotherapy and immunotherapy in osteosarcoma has never been reported, and only in vitro evidence became available very recently, showing that checkpoint blockade in combination with doxorubicin augments tumor cell apoptosis (18), and neoadjuvant chemotherapy reprogrammed the tumor immunologic microenvironment and facilitated the subsequent immunotherapy in osteosarcoma (19).…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine-induced killer (CIK) cells, a frequently studied cell immunotherapy in CRC, are a heterogeneous group of cells obtained from peripheral blood mononuclear cells (PBMCs) stimulated ex vivo with an anti-CD3 antibody and a cocktail of cytokines [ 17 , 18 , 19 ]. These cells share functional and phenotypic properties with NK and T cells and are characterised by rapid expansion ex vivo, non-major histocompatibility complex (MHC)-restricted tumour-killing activity, strong antitumour activity and minimal toxicity [ 17 , 18 ].…”
Section: Cell Therapy Strategies For Crc Treatmentmentioning
confidence: 99%
“…The cytokine-induced killer (CIK) cells, a frequently studied cell immunotherapy in CRC, are a heterogeneous group of cells obtained from peripheral blood mononuclear cells (PBMCs) stimulated ex vivo with an anti-CD3 antibody and a cocktail of cytokines [ 17 , 18 , 19 ]. These cells share functional and phenotypic properties with NK and T cells and are characterised by rapid expansion ex vivo, non-major histocompatibility complex (MHC)-restricted tumour-killing activity, strong antitumour activity and minimal toxicity [ 17 , 18 ]. It has been observed that the combination of adjuvant chemotherapy with sequential infusions of CIK cells significantly improved the progression-free survival (PFS), disease-free survival (DFS) and OS rates of CRC patients [ 18 , 19 ], especially in those with high-risk T4 stage and insufficient duration of chemotherapy (DFS and OS) [ 18 ].…”
Section: Cell Therapy Strategies For Crc Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Adoptive immunotherapy based on genetic engineering of lymphocytes to create chimeric antigen receptormodi ed T (CAR-T) cells has become one of the most promising approaches in the eld of cancer therapy [3]. Several groups have reported preclinical studies in which CRC was treated using CAR-T cells, such as targeting epidermal growth factor receptor-(EGFR-) [4], EpCAM [5] and EGP40 [6] CAR T cells and targeting carcinoembryonic antigen (CEA) CAR cytokine-induced killer (CIK) cells [7]. In addition to preclinical studies, clinical trials using CAR-T cells targeting HER2 [8], TAG-72 [9], CEA [10] and CEACAM5 [11] have also been conducted in patients with CRC.…”
Section: Introductionmentioning
confidence: 99%